2011
DOI: 10.1007/s10549-011-1823-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic approach to identify patterns in phospholipid profiles and define class differences in mammary epithelial and breast cancer cells

Abstract: Breast cancer is the leading cause of cancer-related deaths in women. Altered cellular functions of cancer cells lead to uncontrolled cellular growth and morphological changes. Cellular biomembranes are intimately involved in the regulation of cell signaling; however, they remain largely understudied. Phospholipids (PLs) are the main constituents of biological membranes and play important functional, structural and metabolic roles. The aim of this study was to establish if patterns in the PL profiles of mammar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
97
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 54 publications
14
97
1
1
Order By: Relevance
“…Importantly, previous publications demonstrated that the analysis of lipid extracts obtained from tumor human cells lines or human cancer biopsies showed increased levels of PC and/or PE ether lipids. In fact, these changes are correlated with malignancy and metastatic potential in various cancers [37][38][39][40][41][42]. Some studies demonstrated that plasmalogens are natural antioxidants, as the ether link is more prone to be oxidized than the double bonds usually found in many phospholipids in their fatty acid moiety [9,43].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, previous publications demonstrated that the analysis of lipid extracts obtained from tumor human cells lines or human cancer biopsies showed increased levels of PC and/or PE ether lipids. In fact, these changes are correlated with malignancy and metastatic potential in various cancers [37][38][39][40][41][42]. Some studies demonstrated that plasmalogens are natural antioxidants, as the ether link is more prone to be oxidized than the double bonds usually found in many phospholipids in their fatty acid moiety [9,43].…”
Section: Resultsmentioning
confidence: 99%
“…TG and Chol contents were quantifi ed using the colorimetric kits Liquick Cor-TG and Liquick Cor-Chol (Cormay). PL amounts were estimated from total phosphorous content ( 32 ). TG, Chol, and PL amounts were related to tissue weight used for each extract.…”
Section: Lipidomic Analysismentioning
confidence: 99%
“…TG, Chol, and PL amounts were related to tissue weight used for each extract. PL classes were separated by thin layer chromatography (TLC) using silica gel plates with concentrating zone 2.5 × 20 cm (Merck) ( 32 ) and identifi ed using standards (Avantis). PLs were extracted with chloroform/methanol (2:1, v/v) for mass spectrometry (MS) analysis.…”
Section: Lipidomic Analysismentioning
confidence: 99%
“…Phospholipids, which are the major constituents of cell membranes, play an important role in signal transduction, inflammation, cell proliferation and differentiation [8][9][10], and influence key aspects of cancer phenotype [11,12]. A few papers have reported differences in the lipid profiles of thyroid neoplasms [13][14][15][16], hence this class of compounds could be potentially implemented in classification of thyroid lesions.…”
Section: Introductionmentioning
confidence: 99%